Corrections to "Enhancing Knapsack-Based Financial Portfolio Optimization Using Quantum Approximate Optimization Algorithm" - Huot, Chansreynich; Kea, Kimleang; Kim, Tae-Kyung; Han, Youngsun (IEEE access, 2025)
Presents corrections to the paper, (Corrections to "Enhancing Knapsack-Based Financial Portfolio Optimization Using Quantum Approximate Optimization Algorithm").